Oleoyl Coenzyme A Regulates Interaction of Transcriptional Regulator RaaS (Rv1219c) with DNA in Mycobacteria - Turapov, Obolbek (American Society for Biochemistry and Molecular Biology, 2014)
We have recently shown that RaaS (regulator of antimicrobial-assisted survival), encoded by Rv1219c in Mycobacterium tuberculosis and by bcg_1279c in Mycobacterium bovis bacillus Calmette-Guérin, plays an important role in mycobacterial survival in prolonged stationary phase and during murine infection. Here, we demonstrate that long chain acyl-CoA derivatives (oleoyl-CoA and, to lesser extent, palmitoyl-CoA) modulate RaaS binding to DNA and expression of the downstream genes that encode ATP-dependent efflux pumps. Moreover, exogenously added oleic acid influences RaaS-mediated mycobacterial improvement of survival and expression of the RaaS regulon. Our data suggest that long chain acyl-CoA derivatives serve as biological indicators of the bacterial metabolic state. Dysregulation of efflux pumps can be used to eliminate non-growing mycobacteria.